Cinemática do gás molecular e ionizado em galáxias seyfert e QSOs - Bianchin, Marina (2022)
The supermassive black holes at the centre of massive galaxies can influence their host evolution. During their active phase, the matter in the central parsecs of galaxies flows onto the blackhole creating an accretion disk and ultimately feeding the SMBH. The heated accretion disk releases energy to the surrounding medium in the form of radiation pressure, the so-called Quasar winds, or by relativistic jets of particles. Both these phenomena can push the gas clouds out of the central galaxy region up to kiloparsec scales. The gas outflows observed in different phases can influence the host galaxy. In this thesis, we analyse the gas kinematics in two samples of active galaxies. The first is the Seyfert sample composed of 6 nearby Seyfert galaxies observed with Gemini Near-infrared Integral Field Spectrograph in the J and K bands. We study the kinematics of the ionised gas, traced by Paβ and [FeII] emission lines, and molecular gas, traced by the H22.12µm, in these galaxies. By decomposing the emission-line profiles in distinct kinematic components, we identify ionised gas outflows in four galaxies and molecular outflows traced by distinct kinematic components in two. The mass outflow rates are in the range e 0.005−12.49Myr−1 and the kinetic powers of 1039−1042 ergs−1. We observe signatures of H2 streaming motions towards the centre in three galaxies, but they are not enough to feed the AGN at the current accretion rate. The second is the QSO sample composed of 18 type 2 quasars at z < 0.2 selected from the Quasar Feedback Survey galaxies, observed by the Very Large Telescope Multi-Unit Spectroscopic Explorer. We use the [OIII]5007 as a tracer of the ionised gas outflows. In this sample, we adopt a different analysis approach to identify and characterise the outflows. Multiple Gaussian curves are fitted to the [OIII] emission-line to reproduce the emission-line profile. From the modelled spectra, we derive theW80, the width of the line that contains 80 per cent of the emitted flux, and use this quantity as a proxy to identify the spaxels dominated by outflows as the ones with W80 > 600kms−1. From the 15 galaxies with detected [OIII]5007 emission lines, we identify ionised gas outflows in 13. The masses of ionised outflows are 104 −106M, corresponding to 10-100 per cent of the total mass of ionised gas. The mass outflow rates are in the rages 10−2−100 Myr−1 and the kinetic powers 1038 −1042 ergs−1. By comparing both samples with the literature, we see an increased scatter in the wind scaling relation. The kinetic coupling efficiencies are smaller than the values predicted for the coupling efficiencies in theoretical models. However, this does not imply that the outflows cannot suppress the star-formation in the host galaxy.